Analisis Kebutuhan Fasilitas X-Ray Terhadap Kepadatan Penumpang di Terminal I A Bandara Soekarno Hatta Sesuai dengan Level of Service - Lupi Wahyuningsih (Research and Development Agency of The Ministry of Transportation, 2010)
The length of the queue at the entrance to the departure terminal I-A is certainly going to reduce the sense of comfort for users of transport services in this Soekarno Hatta Airport. According to Director General of Civil Aviation SKEP Number 284/X/1999 About Airport Operational Performance Standards Associated with Service Level (Level Of Service) at the Airport as a basis for price policy air port services. for security checks of passengers and goods every passenger needs a long time wait 3 minutes 9 seconds. Relating to the above, more densely with I-A number of passengers in station, then research must be done about the needs of x-ray facility in accordance with the Level of service mentioned above. from the analysis it is recommended that airport operators to be able to provide the four x-ray facilities at the airport departure terminal I-A of Hatta Airport.